HUBUNGAN ANTARA RISIKO POSISI KERJA DENGANNYERI MUSCULOSKELETAL DISORDERS PADA PEKERJA PABRIK TAHU JAKARTA TIMUR - Widi Nurchoriyah (2023)
Working position is closely related to a person's habits and also the facilities or environment he works. Work position is one of the determining points in analyzing the effectiveness of work. Complaints that are most often found in factory employee complaints are problems in the wrong working position followed by complaints of the musculoskeletal system or commonly called complaints of musculoskeletal disorders (MSDS). Meanwhile, based on the results of a study from the Indonesian Ministry of Health, it illustrates that health problems in Indonesia: there are around 40.5% of workers' illnesses due to work. Based on the survey, there were health problems for around 9,482 workers in 12 locations, followed by complaints of MSDS 16%, Cardiovascular 8% and Neurological 5%, Respiratory 3%, Ear and Throat 1.5%. Objective: This study aims to determine the relationship between work position and musculoskeletal pain in tofu factory workers in East Jakarta. Method: The research method used is quantitative observational with a cross sectional approach. As many as 60 tofu factory workers in East Jakarta participated in this study, the parameters used were REBA (Rapid Entire Body Assessment) to assess work position and the NBM (Nordic Body Map) questionnaire to assess musculoskeletal complaints. Results: this study used the Spearman correlation test to obtain a value of p = 0.000 (<0.05) and the value of the correlation coefficient of the two variables was r = 0.454. Conclusion: This indicates that there is a relationship between.